TRANSFORMASI POLA TATA RUANG RUMAH TRADISIONAL JAWA KE DALAM POLA TATA RUANG RUMAH TINGGAL SEDERHANA - Joko Budiwiyanto (Pendhapa, 2011)
The research on "The lnteriorDesign Transformation of a Javanese Traditional house into basichousing in Surakarta â€ is a qualitativeÂ»descn'ptive research. The research was focused on interpretingthe interior design transformation of a house and their inÃ¯Â¬â€šuencing factors. The location for theresearch was Surakarta and its surroundings. The source ofinformation covers written and verbalsources, artifacts, and recordings. The triangulation method of sources and review informantwere used to Ã¯Â¬nd out the accuracy and reliability of the data. The data was analyzed using atechnique based on an interactive model.The research results show that a Javanese traditional house consists of the rnain house and theadditional house. The main house consists of pendapa (open pavilion-like veranda) pringgitan(section of a traditional-style house), kuncung, tratag, dalem ageng, sentong kiwa (small innerroom on the left), senthong tengen (small inner room on the right), and senthong tengah (smallinner room in the middle). The additional house consists of gandhok (wing of a house), Gadri,Pawon (kitchen) and Pekiwan (lavatory). The interior design of basic housing consists of onebedroom, one versatile room, and one bathroom. The interiordesign of Javanese traditional houseis divided based on social strata and custom while that of Basic Housing is divided based onpractical and pragmatic functions. The transformation can be traced back to the transformation ofform, function, meaning and the interior design. The interior design transformation of traditionalJavanese house into basic housing is caused by some factors such as the cultural factor comingfrom the outside (external), social condition of the society (internal practical function and theowners Ã¯Â¬nancial condition.Key words: transformation, interior design, Javanese house, basic housing